Borders of Wealth and Poverty: Ideas Stimulated by Comparing the Mediterranean and U.S.-Mexico Borders - Josiah Heyman; Natalia Ribas-Mateos (Archivio Antropologico Mediterraneo)
How can anthropologists and sociologists share ideas and knowledge on the Mediterranean and U.S.-Mexico borders to deepen insight and understanding? The best-known comparison is militarized border enforcement, plus humanitarianism, posed against asylum seeking and irregular migration. But, more complex mobility occurs at these borders, including privileged and other differentiated and sorted mobilities. Interwoven with these mobilities, commerce of many scales and degrees of legality occurs, supporting complicated cultural worlds of informality and exchange. Borders require not just a political analysis, but also attention to capital. Importantly, borders (immediate and extended) have become increasingly important sites of export-oriented production in the world economy. The processes of interchange at borders, in turn, support important urban zones and other communities that merit close ethnographic study for their social and cultural complexity.